Rationale of CAB (Communication Activities for Beginners) - Laing, Neville ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
A variety of games for beginning second language learners are described. The games are designed to develop the student's confidence in communicating in the target language and to help establish his interlanguage. They include: a bilingual guessing game, to be played by a learner and a native speaker; a game to match words, pictures, and definitions; a conundrum in the form of a physical puzzle; a description/object guessing game and variations; a geography guessing game; an exercise in reconstructing a story from mixed sentences; and a word/picture matching game. Several related books are listed. (MSE)
ERIC Note: Paper presented at the Annual Meeting of the Japan Association of Language Teachers (Kyoto, Japan, September 1985).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Class Activities; Communication Skills; Educational Games; Games; Group Activities; Interlanguage; Introductory Courses; Learning Activities; Memorization; Second Language Instruction; Vocabulary Development; Guides, Classroom -- Teacher; Speeches/Meeting Papers